Lateral thrust in all-steel buckling-restrained braces: Experimental and FEM results. (15th June 2020) - Genna, Francesco
Highlights: The results of eleven new tests on eleven nominally identical BRB samples are presented. The axial force-axial displacement curves show a scatter compatible with the experimental setup. The lateral thrust–axial displacement curves show a scatter one order of magnitude higher than the previous one. Frames of the relative motion between core and external restraining profiles show very little relative slip. Readings from longitudinal strain gages suggest a von Kármán buckling type. Abstract: The lateral thrust — the total contact force exerted by the buckled core of a buckling-restrained brace (BRB) against its restraining profiles — in bolted all-steel BRBs was studied mainly by means of laboratory tests. The primary purpose was to obtain a better understanding of the "predictability" of the lateral thrust for a given set of boundary conditions. Eleven nominally identical all-steel, reduced-scale BRB samples were subjected to the same cyclic loading, and data were recorded concerning (i) the value of the total lateral thrust, (ii) the relative slip between the buckled core and the restraining surfaces, and (iii) the longitudinal strain at opposite faces of the buckled core. A very high scatter among the peak values of the lateral thrust was observed. The experimental results concerning points (ii) and (iii) were integrated by the results of a refined 3D Finite Element analysis. Very little core-restraining profiles relative slip was observed in the tests. The elastic-plastic core buckling seems to be of the von Kármán type, i.e., with simultaneous loading and unloading at the opposite sides of the core.